(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This report discusses the configuration of some preparatory and auxiliary commands for the Fanuc 18i TB CNC system for a counter-spindle lathe using special macros called Vericut macros. In most cases, this is necessary because the Vericut library of machines and CNC systems does not have the specific machine and system or do not correspond to the actual ones, i. e. there is no match between them. The need to configure the CNC control system is related to the fact that it is possible to perform simulation, optimization and verification of control programs in a virtual environment before proceeding to the processing of workpieces on the real machine.